IMPROVEMENT OF THE METHODOLOGY OF FORMATION OF PERSONAL AND PROFESSIONAL QUALITIES OF FUTURE TEACHERS OF PRESCHOOL EDUCATIONAL ORGANIZATIONS (Universal International Scientific Journal, 2026)
This article examines the improvement of methodology for developing the personal and professional qualities of future preschool teachers. It explores the importance of professional orientation, communicative and moral qualities of teachers, as well as the role of competency-based, activity-based, and student-centered approaches in training preschool education specialists.
Keywords: preschool education, teacher, professional qualities, personal qualities, training methodology, competency-based approach, activity-based approach, student-centered approach, pedagogical activity, professional training, communication skills, pedagogical competence, personal development.